2006
DOI: 10.1038/sj.embor.7400773
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c‐d regulates developmental apoptosis in the Drosophila retina

Abstract: The role of cytochrome c (Cyt c) in caspase activation has largely been established from mammalian cell‐culture studies, but much remains to be learned about its physiological relevance in situ. The role of Cyt c in invertebrates has been subject to considerable controversy. The Drosophila genome contains distinct cyt c genes: cyt c‐p and cyt c‐d. Loss of cyt c‐p function causes embryonic lethality owing to a requirement of the gene for mitochondrial respiration. By contrast, cyt c‐d mutants are viable but mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 33 publications
3
73
1
Order By: Relevance
“…When raised at 25°C, each ommatidium adopts a rigid hexagonal pattern in the wild-type flies at 40 h APF (after pupa formation), and anti-Armadillo staining can visualize each cell in the developing retina. 32 To quantify the number of IOCs in the developing retina, a hexagonal target area is defined by connecting the center of six ommatidia surrounding a central ommatidium (Figure 2A a). 33 GMR>white …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When raised at 25°C, each ommatidium adopts a rigid hexagonal pattern in the wild-type flies at 40 h APF (after pupa formation), and anti-Armadillo staining can visualize each cell in the developing retina. 32 To quantify the number of IOCs in the developing retina, a hexagonal target area is defined by connecting the center of six ommatidia surrounding a central ommatidium (Figure 2A a). 33 GMR>white …”
Section: Resultsmentioning
confidence: 99%
“…At least 30 hexagonal target areas were scored from three to six different flies for each experiment as reported by others. 32 …”
Section: Methodsmentioning
confidence: 99%
“…In one study, silencing expression of either or both Drosophila cytochrome c proteins was found not to affect apoptosis in the fly, and addition of either recombinant forms of these proteins or whole mitochondrial extracts to cell-free systems failed to significantly activate caspases in Drosophila cell lysates, although addition of recombinant Drosophila cytochrome c does yield caspase activation in mammalian lysates. [42][43][44] However, studies on flies lacking d-cyt-c, one of the Drosophila cytochrome c genes, found severely delayed apoptosis in the developing retina, 45 and a genetic screen found that mutations in d-cyt-c reduced caspase activation during spermatid individualization, 46 an effect phenocopied by ARK or DRONC loss-offunction mutations. An earlier study found that an otherwise hidden epitope of cytochrome c is presented early in the Drosophila apoptotic program, although this putative conformational change is apparently caspase dependent and proceeds without release of cytochrome c from the mitochondria.…”
Section: Conservation Of a Mitochondrial Role In Cell Death: A Fly Inmentioning
confidence: 99%
“…There is mounting evidence to challenge this view: (1) the Drosophila Bax/Bak ortholog debcl is required for some developmental apoptosis [28], (2) developmental apoptosis in the retina and non-apoptotic activation of caspase require Cyt-c [29][30][31] and (3) active apoptosome complexes are constantly subjected to feedback inhibition in living cells [20]. This suggests that activation of the apoptosome is not constitutive and that the apoptosome is activated by a signal (Cyt-c or another factor) in dying cells.…”
Section: The Role Of Mitochondria In Apoptosismentioning
confidence: 99%